LOCALIZATION AND TRANSLATION OF MCDONALD’S WEB PAGES: CROSS-CULTURAL ADAPTATION - Gonçalves, Vitor (2023)
This article was written as part of the curricular unit on Localization of Software and Web Pages of the Master's in Translation at the School of Education of the Polytechnic Institute of Bragança. We were interested in reflecting on the need to rethink translations not only from a linguistic perspective, but also from a cultural one, essentially because culture is a fundamental and unique pillar in each nation and absolutely vital to its identity. In this sense, a research focused on the cultural dimension became important, namely by analyzing the McDonalds web pages of each country and the respective perceived cultural adaptations. The analysis was supported by a methodology of a comparative study of the company’s websites, namely in countries on different continents. This analysis was based essentially on the observation and review of the literature that was carried out through a bibliographical research that was guided by a set of criteria previously established with the aim of refining the research. The results presented through a comparative table containing the evaluation criteria, highlight mainly: products; marketing campaigns; multimedia presentation and effects, among others.